The effect of some mechanical properties by using optical means to develop the kinematic index and some biomechanical variables for the accuracy of high-flying aiming with a hand ball - Majeed Salall, Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
The importance of biomechanics as the science concerned with the study of movement for the athlete by analyzing, clarifying, improving, and developing a lot of mathematical skills based on the latest tools and devices represented by imaging devices that achieved accurate objective results in motor performance, as well as the importance of using visual aids in units, were discussed. Educational, which works to improve the level of performance, especially the accuracy of remote aiming by jumping high with the handball.The importance of the research was evident in the fact that learning is not complete without the use of important educational aids that demonstrate the importance and effectiveness of mechanical properties and the extent to which they are effectively applied during the skill of remote correction by jumping high with a handball.This section also included the research problem, which was embodied in the study of the effectiveness of mechanical properties based on the optical means system in order to develop the kinematic transmission index and some biomechanical variables for the accuracy of shooting by jumping high with the hand reel. As for the research goals, they are as follows:1. Identifying the effect of mechanical properties by using the optical means system applied within an educational curriculum in developing the kinematic transmission index for the accuracy of shooting by jumping with a handball.2- Identifying the differences in the values of some biomechanical variables for the accuracy of shooting by jumping aloft with the handball between the pre- and post-tests of the experimental and control groups.3- Identifying the differences in the values of some biomechanical variables for the accuracy of shooting by jumping high with the handball between the experimental and control groups in the post-tests. As for the research hypotheses, they are as follows:1. The mechanical properties of using the optical aids system applied within the educational curriculum have a positive effect on the development of the kinematic transmission index for the accuracy of shooting by jumping high with the handball.2- The existence of differences in the values of some biomechanical variables for the accuracy of shooting by jumping aloft with the handball between the pre- and post-tests of the control and experimental groups.3. There are differences in the values of some biomechanical variables for the accuracy of shooting by jumping high with the handball between the experimental and control groups in the post tests.